Pelatihan Analisis Potensi Ekonomi Berbasis Agribisnis Berkelanjutan Desa Joho Kecamatan Semen Kabupaten Kediri - Solikin, Nur; Yuniati, Erna; Linawati, Linawati; Kusuma, M. Putra Hadi; Rohman, Alfan Nur (Universitas Nusantara PGRI Kediri, 2024)
The activity aims to explore rural potential in developing sustainable agribusiness by considering natural resources and human resources as one of the strategic ways to improve a sustainable rural economy. The various potentials possessed by villages are understood to be one option for strengthening the rural economy in a sustainable manner by actively involving community components that will bring about the impact of change. The chosen approach is a mixed method participatory approach. The findings were known to participants of the potential analysis training activity in Joho Village, Semen District: 1) the participants' initial knowledge (pretest) about the village's economic potential and opportunities was still low, showing an increase in score of 28.8 after taking part in the socialization, 2) after receiving knowledge of business opportunities (agribusiness integration) the participants motivated to determine the village's potential economic efforts.